Determination of Workload, Work Stress and Related Factors in Nursing Home Workers during the COVID-19 Pandemic in Turkey - Akdeniz, Ş.; Çoban, M.; Koç, O.; Pekesen, M.; Korkmaz Yaylagul, N.; Sönmez, S.; Yetiz, F. (MDPI, 2023)
COVID-19 has caused a major crisis all over the world. To manage this crisis, a fixed shift system was applied to nursing home staff in Turkey to protect nursing home residents from the COVID-19 pandemic. Staff were not allowed to leave the institution during fixed shifts. It is thought that this practice for the COVID-19 outbreak, while protecting nursing home residents on the one hand, increased the workload and related stress of nursing home staff on the other hand. To the best of our knowledge, there is no study examining the workload and stress caused by the COVID-19 pandemic for nursing home staff in Turkey. The aim of this study was to examine the level of workload and work stress experienced by staff working in nursing homes during the COVID-19 pandemic in Turkey. Methods: A cross-sectional research design was used in the study. The sample of the study consisted of nursing home personnel working in nursing homes in the provinces of Istanbul, Ankara, Izmir and Antalya between October 2021 and January 2022. A personal information form and a workload and stress scale were used for collecting the data. Cluster analysis was performed with SPSS software. Results: In total, 154 nursing home personnel participated in the study. A statistically significant difference was found between the mean age of the two clusters. The first cluster was described as “old” and the second as “young”. Statistically significant and high values were found in the quantitative workload, qualitative workload, job organization, social work area and fatigue factors in the nursing home staff in the older participant cluster. Conclusion: The results of this study provide new information about the concepts of workload and work stress experienced during the COVID-19 pandemic in Turkey, which will serve as a guide for the management of future pandemics. Therefore, this study will contribute to the strategies to be followed in future pandemics in Turkey. © 2022 by the authors.
Keywords: Covid-19; Nursing Home Staff; Pandemic; Work Stress; Workload; Covid-19; Disease Spread; Epidemic; Health Worker; Working Conditions; Adult; Article; Coronavirus Disease 2019; Cross-Sectional Study; Fatigue; Female; Human; Human Experiment; Job Satisfaction; Job Stress; Male; Mental Health; Nursing Home; Nursing Home Personnel; Organization; Pandemic; Questionnaire; Social Work; Turkey (Republic); Work Environment; Workload; Epidemiology; Pandemic; Turkey (Bird); Workload; Ankara [Turkey]; Antalya [Turkey]; Istanbul [Turkey]; Izmir [Turkey]; Turkey; Covid-19; Cross-Sectional Studies; Humans; Nursing Homes; Occupational Stress; Pandemics; Turkey; Workload